Pengenalan Penerapan Ergonomi Kantor dan 5S Kepada Pegawai Administrasi Kelurahan X - Sarvia, Elty; Halim, Winda; Novi, Novi; Yudiantyo, Wawan; Christina, Christina; Soly, Silviana (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Office ergonomics talk about how to make the work area in the office suitable for people who work and support the work activities they do. Meanwhile, 5S (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) is a system that makes work activities better and of higher quality. If these two principles are applied properly to an office activity, it will certainly increase the efficiency and effectiveness of the work being carried out. The introduction of the two principles was carried out for Kelurahan X employees. Information was provided through an interactive webinar format through the Zoom Meeting platform. The purpose of this activity is to provide an understanding of the importance of Ergonomics in the office and the importance of implementing 5S to the employees of the X Village office. In the early stages of implementation, information is provided through the lecture method and collects data related to the knowledge that participants currently have using a questionnaire using Google Form, then in the next stage, participants are asked to actively participate in the application of the material that has been presented previously. In the final results of data collection, it was proven that participants had understood the benefits of applying these principles by increasing the percentage of participants' understanding obtained from the final questionnaire